Spatial Characteristics of Mesoscale Plasma Flow Perturbations and Accompanying Electron Precipitation in the High‐Latitude Ionosphere. Issue 12 (7th December 2019) - Chen, Yun‐Ju; Heelis, Roderick A.
Abstract: The spatial characteristics of mesoscale plasma perturbations in the high‐latitude ionosphere are important considerations for a more complete description of the energy deposition from the magnetosphere. In this study, ion drift and particle precipitation measurements from the Defense Meteorological Satellite Program F17 satellite during local summer seasons in 2012 are used to examine the flow perturbations and their closure paths and the particle precipitation associated with them. The closed circulation associated with a flow perturbation is identified from the potential distribution and can be described by a single‐cell or a two‐cell configuration with characteristic spatial scale sizes between 100 and 600 km and 200 and 1, 200 km, respectively. Observations suggest that an asymmetry in space and flow speed is frequently seen with faster flows in a narrower region and slower return flows in wider adjacent regions. For a single‐cell configuration, the faster flows are preferentially sunward and in the same direction as the background convection, and the weaker return flows are preferentially duskward/dawnward of the potential maxima/minimum. For a two‐cell configuration, the faster flow is seen in the central region and also tends to follow the background convection with weaker return flows on the two sides. Except in the region poleward of the convection reversal boundary, 0.5–3 keV electron precipitation, displaying the same spatial asymmetry as the flow perturbation, is frequently seen in a single cell around a potential minimum on the dusk side. Key Points: Asymmetry in space and flow speed is seen with faster flows in a narrower region and slower return flows in wider adjacent regions Faster flows of plasma vortices are preferentially in the same direction as the background convective flow 0.5–3 keV electron precipitation is frequently seen near potential minima with the same spatial asymmetry as the flow perturbations at dusk